The experiences of relationships and self-esteem development in an expressive self-esteem group intervention for adolescent females who have been sexually abused - Visser, M.J. (Maretha Johanna) (University of Pretoria, 2015)
Dissertation (MA (Counselling Psychology))--University of Pretoria, 2015.